Eusociality and Senescence: Neuroprotection and Physiological Resilience to Aging in Insect and Mammalian Systems - Giraldo, Ysabel Milton; Muscedere, Mario L.; Traniello, James F. A. (Frontiers in Cell and Developmental Biology, 2021)
Are eusociality and extraordinary aging polyphenisms evolutionarily coupled? The remarkable disparity in longevity between social insect queens and sterile workers – decades versus months, respectively – has long been recognized. In contrast, eusocial naked mole rat breeders and non-breeders are both extremely long-lived – roughly 10 times longer than mice. Is this robustness to senescence associated with social evolution and shared mechanisms of developmental timing, neuroprotection, antioxidant defenses, and brain metabolism? Focusing on brain senescence, we examine correlates and consequences of aging across two divergent eusocial clades and how they differ from solitary taxa. Chronological age and physiological indicators of neural deterioration, including DNA damage or cell death, appear to be decoupled in eusocial insects. In some species, brain cell death does not increase with worker age, and DNA damage occurs at similar rates between queens and workers. In comparison, naked mole rats exhibit characteristics of neonatal mice such as protracted development that may offer protection from aging and environmental stressors. Antioxidant defenses appear to be regulated differently across taxa, suggesting independent responses to life history and environment. Eusocial insects and naked mole rats appear to have evolved different mechanisms that lead to similar senescence-resistant phenotypes. Careful selection of comparison taxa and further exploration of the role of metabolism in aging can reveal mechanisms that preserve brain functionality in eusocial species.